Cooperative Learning Model In Teaching Foreign Languages - Yusuf, Rusydi Muhammad; Hidayat, Syarif - (Jurnal Ilmiah Mandala Education (JIME), 2023)
Cooperative learning method defined as the instructional use of small groups, so the students work together to maximize their own and the other’s learning. Cooperative learning was based on the social interdependence on individual interaction within a given situation which, in turn, affects the outcome of that interaction. In cooperative learning, the development of interpersonal skills was as important as the learning itself. Cooperative learning was not assigning a report to a group of students where one student did all the work and the others put their names on the product as well. Cooperative learning involves much more than being physically near other students, discussing material, helping, or sharing material with other students. The aim of This research is to explore how the cooperative learning method be implemented in daily teaching language activities, what is cooperative learning method, what are the strengths and the weaknesses using cooperative learning method in teaching language. So it could be concluded that the application of this model in teaching language can increase student activity, so that student learning outcomes will be better because students who always complete all teaching and learning activities so that they can master the material being studied